Analisa Kesadahan Total (CaCo3) Pada Air Sumur Bor Di Lingkungan Dusun II Desa Sei Rotan Gg Pasar Baru Kecamatan Percut Sei Tuan Dengan Metode Kompleksometri - Siahaan, Maniur Arianto; Sipayung, Apriska Dewi; Winda Irawati Zebua (Universitas Sari Mutiara Indonesia, 2024)
Water in nature contains various dissolved and insoluble substances. If the contents contained in the water do not harm human health, the water can be considered clean. Considering the important role of water, it is very necessary to have a water source that can provide good water in terms of quantity and quality. The use of drilled well water is one of the alternatives used by humans to meet the need for water for both household and industrial needs. Hardness is one of the chemical parameters that can reduce groundwater quality. The level of water hardness is basically determined by the amount of calcium (Ca2+) and magnesium (Mg2+). This research aims to determine the total hardness of drilled well water in Dusun II, Sei Rotan Village, Gg Pasar Baru, Percut Sei Tuan District, whether it meets the requirements of the Republic of Indonesia Minister of Health Regulation No. 32 of 2017. Descriptive observations of the samples used were taken directly from drilled well water in Dusun II, Sei Rotan Village, Gg Pasar Baru, Percut Sei Tuan District, randomly with 10 samples using the complexometric method. The total hardness (CaCO3) of drilled well water that has been tested is 48.47 mg/L to 268.92 mg/L. The total hardness (CaCO3) of drilled well water in Dusun II, Sei Rotan Village, Gg Pasar Baru, Percut Sei Tuan District, was identified that all samples met the requirements in accordance with RI Minister of Health Regulation No. 32 of 2017. The maximum level obtained was 500 mg/L.